Development of modified polyacrylonitrile fibers for improving tribological performance characteristics of thermoplastic polyurethane material in water‐lubricated sliding bearings. (18th August 2020) - Liang, Xiang; Guo, Zhiwei; Tian, Jun; Yuan, Chengqing
Abstract : Thermoplastic polyurethane (TPU) is one of the most popular marine bearing materials because of its excellent characteristics. However, severe wear often occurs under some extreme conditions. In order to improve the service life of bearing material, this work introduced the polyacrylonitrile (PAN) fiber as a reinforcement material to further enhance TPU tribological properties. Considering that the bearing material does not process self‐lubricating or cannot form a stable water film under some working conditions, the PAN fiber was hydrophilically modified to alleviate this problem. The effects of fiber addition, operation speed, and applied load on the tribological properties of the composites were examined by using a tribo‐tester. The friction coefficient of the samples, the surface morphology after rubbing, and the wear loss, and so on, were also comprehensively analyzed. It was found that the friction coefficient of 30% modified PAN fiber at 500 r/min and 0.8 MPa load was 0.08, and its friction coefficient was 81.8% lower than the pure sample under the same working condition, this is mainly due to the high hydrophilicity of the modified PAN fiber, which makes it easier to form a water film between the composite material and the copper disc. Furthermore, adhesive wear occurred in unmodified samples, while modified samples contained abrasive wear. This new material modification method and design idea can be used for improving the performance of water‐lubricated bearing materials.